INSENTIF PELAPORAN DAN PERENCANAAN PAJAK PERUSAHAAN - Wenny Adelia Agasi; Aditya Septiani (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of corporate tax position uncertainty, tax expertise, and performance-based remuneration incentives of its key management personnel on corporate tax avoidance. This study uses two control variables are ROA and external auditors. The population in this study consists of all listed firm in Indonesia Stock Exchange in 2013. The sampling method in this research is purposive sampling. Criteria for firm is a manufacturing company and a company that serves the financial statements with currency. Another criteria is the firm must have complete data and support the implementation of research. Total sample in this study is 82 data. OLS regression used to be analysis technique. The empirical result of this study show that uncertainty of a firm’s tax position and the performance-based remuneration incentives of its key management personnel are positively significant influenced on corporate tax avoidance. Tax expertise has no influence on corporate tax avoidance.